Primer registro en Cuba de la pudricion de la vaina del arroz por sarocladium oryzae (Sawada) Gams Hawks - Sandoval, I.=700 1 Lopez, M.O.; Bonila, T.; Tomas, Y.
(Es, En)
Ilus., 20 ref.
Keywords: ORYZA SATIVA; SAROCLADIUM; PODREDUMBRES; VAINA FOLIAR; PANICULA; CUBA